社会记忆与身份认同 ：新加坡连续剧《红头巾》案例分析 = Case study of TV series Samsui Women : analysis of the construction of social memory and national identity - 陈嘉懿 Tan, Jia Yi (Nanyang Technological University, 2020)
本文针对早年自中国飘洋过海到新加坡从事建筑行业的华人女性移民来进行研究，而这群女性劳工移民被称之为“红头巾”。笔者认为“红头巾”符合官方论述的建国功臣，在经过时代的变迁后，通过她们的生命经验来揭露新加坡如何利用女性移民的生活经验来建构国家认同及自我历史的论述。新加坡在2014年提出的建国一代配套（Pioneer Generation Package）将“红头巾”归纳为新加坡的建国一代，并且她们还能享有其中的福利。“红头巾”在家乡的生活概况贫困，再加上自然灾害的突袭，而当时东南亚国家的移民政策条件宽松，导致她们纷纷移民到新加坡来。“红头巾”的功劳被新加坡认可，而她们这群女性移民形象也被中国官方记录下来。中国与新加坡都运用各自不同的方式来纪念“红头巾”年轻时所立下的功劳。新加坡新传媒在1986年制作而播出的《红头巾》连续剧显示“红头巾”在新加坡所形成的集体记忆促使新加坡把这些记忆归类为新加坡的社会记忆。因此，新加坡政府将这群“红头巾”的生活经历融入国家的社会历史的建构中，将她们的精神传扬给年轻一代的新加坡人。最后，本文将会对“红头巾”这个群体在新加坡继续发扬光大的过程来进行反思。 This thesis aims to provide an insight of the southern Chinese female immigrants who travelled by sea to Singapore to work as female construction workers in the early years. This group of female labourers are known as the “Samsui women”. This thesis portrays the “Samsui women” as nation building heroes. As the society improves, Singapore authorities can make use of the Samsui women’s life experiences to construct national identity and write our self-history. The Pioneer Generation Package introduced by Singapore in 2014 categorizes the Samsui women as Singapore’s pioneer, and they get to enjoy the benefits. The Samsui women’s lives were poor back in their hometown, along with natural disasters and loose immigration policies in the nearby Southeast Asian countries, these were the reasons that prompted them to migrate to Singapore. The fruitful labour of these Samsui women are recognised by Singapore, and their image of female immigrants were also recorded officially by the Chinese officials. Both countries have their own methods of commemorating the credits of Samsui women when they were young. The Singapore Broadcasting Corporation (now Mediacorp Pte Ltd) produced a 24-episode historical drama serial titled Samsui Women in 1986, and it showed the collective memory formed by the Samsui women in Singapore, which was later then classified as Singapore’s social memory. Thus, the life experiences of these Samsui women were incorporated into the country’s social and historical identity construction, and passed on their spirit to the younger Singaporeans. Finally, this thesis will reflect the process in which the Samsui women will be remembered and how they will continue to flourish in Singapore.